AESTHETICS OF ANIMATED MOVIE POSTER ILLUSTRATION "SI JUKI THE MOVIE" - I Made Hendra Mahajaya Pramayasa; Gede Pasek Putra Adnyana Yasa; Gede Lingga Ananta Kusuma Putra (Journal of Aesthetics, Design, and Art Management, 2023)
Purpose: In animated films, posters serve as a means to convey story illustrations. The visuals of the poster become an attraction for the audience or fans. Signs help the audience understand the purpose and message to be given. The information content of animated film works can be displayed through carefully arranged images or text and apply elements of art and art principles to create beauty. Research methods: To deepen the understanding of the value of beauty contained in the poster that is the focus of the research, the author analyses the illustrations presented through the description of aesthetic elements and principles concerning Herbert Read's objective theory. This article describes the accurate beauty values reflected in the objects in the poster of "Si Juki The Movie, Committee for the End of Days. This article presents a conclusion about aesthetics that can be identified through the elements and principles of aesthetics contained in the work. Findings:Film posters have the potential as a means to disseminate information using aesthetically designed illustrations of images and text. Through applying aesthetic elements and principles, movie posters can create a value of beauty that visualising shapes, colours, and motifs can easily understand. Based on the analysis, the animated movie poster "Si Juki The Movie" has a beauty implied in the aesthetic elements contained in the shapes, colours, and motifs displayed on the sign. Implications: The results of this research are expected to increase public knowledge about the elements and principles of aesthetics interpreted through objective beauty in an animated film poster work.